El desarrollo de las habilidades sociales en las relaciones interpersonales en los niños de 5 años - Bravo Quimis, Amarilis Soraya (2020)
The research work is focused on determining the development of social skills in first grade children of the Arnulfo Jaramillo Sierra Fiscal Education Unit and interpersonal relationships through the use of playful activities to encourage students to express their emotions. feelings and Strengthen the bonds of affection with their classmates, teachers and parents, for the development of the project various instruments were used such as the survey, interview, observation sheet, methods, empirical, inductivedeductive, which serve to measure the problem studied, according to the updated results through the teachers' survey, it is evident the need to use new pedagogical teaching methods that are according to age to socialize with children in places where they do not affect physical integrity and can develop them safely, with the purpose of providing teachers with new you use methodological tools that allow them to make the most of the classes to encourage children by involving parents in social integration by creating a stronger bond………